Industrial and agricultural land uses affected the water quality and shaped the bacterial communities in the inflow rivers of Taihu Lake - Liu, Shuang; Lu, Jing; Adriaenssens, Evelien M.; Wang, Jianjun; McCarthy, Alan J.; Sekar, Raju (Frontiers in Environmental Science, 2024)
Taihu Lake is the third-largest freshwater lake in China and is vital as a drinking water source, as well as for irrigation water, flood control, and other functions. Taihu Lake is connected to many inflow rivers, which contribute to the water resource but also to its pollution. Investigating the correlation between water quality, bacterial community structure, and land use types is essential for pollution control. Yet, few studies have been conducted on all the major inflow rivers of Taihu Lake. This study aimed to assess the bacterial community composition of major inflow rivers of the lake and determine the relationship between the bacterial community, water quality, and land use. Water samples were collected from ten inflow rivers across four seasons in 2019-2020. DNA extracted from the samples was used for 16S rRNA gene-targeted next-generation sequencing to determine the bacterial community structures. Thirteen physicochemical and microbiological parameters were used to assess the water quality, and the land-use pattern surrounding each sampling location was also profiled. The bacterial community composition demonstrated significant seasonal variation. In summer, the community variation was correlated with chlorophyll a, pH, and phosphate-P, and electric conductivity, nitrate-N, and ammonium-N in winter. Rivers in the northwest were more nutrient-rich than those in the southwest. The industrial, residential, and agricultural land-use categories correlated strongly with the bacterial community composition and water nutrient parameters. Accordingly, farmland drainage, untreated domestic wastewater, and industrial pollution were identified as the major objectives for more effective water quality management in the region.